2022
DOI: 10.3389/fmedt.2022.893056
|View full text |Cite
|
Sign up to set email alerts
|

Advances in lipid-based nanocarriers for breast cancer metastasis treatment

Abstract: Breast cancer (BC) is the most common cancer affecting women worldwide, with over 2 million women diagnosed every year, and close to 8 million women currently alive following a diagnosis of BC in the last 5-years. The side effects such as chemodrug toxicity to healthy tissues and drug resistance severely affect the quality of life of BC patients. To overcome these limitations, many efforts have been made to develop nanomaterial-based drug delivery systems. Among these nanocarriers, lipid-based delivery platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Our confocal and flow cytometry experiments demonstrated that this may be caused by the interaction of NC, NLC, and NE lipid nanocarriers within MDA-MB-231 and MCF-7 cells. To get around these issues, the usage of nanocarriers is being researched.79 [92]. Researchers describe a novel class of hybrid nucleoside-lipid-based sorafenibbased nanoparticles.…”
Section: Lipid Based Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Our confocal and flow cytometry experiments demonstrated that this may be caused by the interaction of NC, NLC, and NE lipid nanocarriers within MDA-MB-231 and MCF-7 cells. To get around these issues, the usage of nanocarriers is being researched.79 [92]. Researchers describe a novel class of hybrid nucleoside-lipid-based sorafenibbased nanoparticles.…”
Section: Lipid Based Nanocarriersmentioning
confidence: 99%
“…The outcomes illustrate the utilization of therapeutically relevant radiation doses to facilitate concurrent receptor-mediated enhanced chemotherapeutic administration, while minimizing systemic toxicity. 92,105,106,107,108 .…”
Section: Micellesmentioning
confidence: 99%